Tanggung Jawab Hukum Produsen atas Makanan Berbahaya dalam Perspektif Strict Liability: Studi Kasus Roti Okko - Aulia Lorenza; Elia Sazeti; Syarifah Widia (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the legal responsibility of producers for the circulation of hazardous food products through a strict liability approach, with a case study on the Okko Bread product which was proven to contain sodium dehydroacetate (NDA)—a substance prohibited for use in bread based on BPOM regulations. The research method used is normative empirical, namely combining analysis of laws and regulations, especially Law Number 8 of 1999 concerning Consumer Protection, with empirical facts from the findings of the Food and Drug Supervisory Agency (BPOM) and the responses of producers. The results of the study show that producers do not fully carry out their legal obligations, both in terms of information transparency and responsibility for consumer losses. The application of the strict liability principle still faces obstacles in implementation, mainly due to weak supervision, low legal awareness of producers, and minimal consumer literacy. These findings indicate the need to strengthen regulations, increase legal sanctions, and educate the public so that the principle of absolute liability truly provides fair protection for consumers. This study emphasizes the importance of integration between law enforcement, business ethics, and the active role of society in creating an effective and sustainable consumer protection system.